Islamophobia in the West: A Critical Discourse Analysis of Imran Khan’s UNGA Speech - Javaid, Meesam (Religions, 2022)
The tragic and horrendous attack on the World Trade Center also served to construct an unmistakable shape to Islamophobia in the West. It worked as fuel for the already-lit fire of Islamophobia and aggravated the situation with numerous indiscriminate attacks on Muslims. The situation worsened with George Bush’s unequivocal statement: "either you are with us or against us". This was the call for a cultural war between the West and Muslims framed by the Us versus Them schemata. This research has analyzed the speech of Imran Khan which he delivered at the 74th session of the United Nations General Assembly, employing van Dijk’s Ideological Square Model with a specific focus on NVivo 12 Plus to inspect the magnitude of the impact of linguistic memorandums from authoritative institutes. The researchers have investigated the lexicalization of Khan’s speech to explore how he uses language to sketch the picture of the West as "them" parallel to "us". His rhetoric is critically examined through the micro and macro-strategies of the Ideological Square Model. The findings reveal that instead of challenging and interrogating the Us versus Them schema that permeates Islamophobia, Khan himself uses the very same schema to show ideological differences between the West and Muslims.